Agency Theory Related to Trustworthy Profit Sharing in Suppressing the Adverse Selection Problem - Warliana, Lisna; Abdullah, Muhammad Wahyuddin (El-Barka Journal of Islamic Economics and Business, 2021)
This study aims to determine how agency theory is related to the trustworthy profit sharing in suppressing the adverse selection problem. This research is a qualitative research. The type of research that researchers use is library research. Library research is a form of research carried out by collecting various kinds of references which are the main source for conducting research, references which are the primary sources in this research are articles published in journals, and other written articles. The results of this study explain that when the company divides the ownership structure and also the management of the company, there will be problems in it, the problem that arises is that there is an agency problem. Agency problems are divided into  two forms, namely moral hazard and also adverse selection. One way to solve this problem is to apply the concept of a trustworthy profit sharing.